Evaluación del comportamiento de cultivares de arroz frente al “Entormchamiento” (Rice Stripe Necrosis Virus) - Asselborn, Miriam; Ayala, Jorge Omar Antonio; Kruger, Raúl; Pachecoy, Maria Ines; Pedraza, Maria Virginia (Asociación Argentina de Fitopatólogos, 2021)
Póster